2005
DOI: 10.5194/aab-48-40-2005
|View full text |Cite
|
Sign up to set email alerts
|

Fattening, carcass and meat quality traits of hybrid pigs as influenced by MHS genotype and feeding systems

Abstract: Abstract. Within the scope of a growth study fattening, carcass and meat quality traits of MHS gene carriers (Nn) and homozygous negative (NN) castrated male pigs (n=96) kept under two different feeding systems were investigated. The experimental group was intensively fed during the whole fattening period (age 10 to 26 weeks). According to feeding recommendations for barrows, the control group was also fed intensively from 10th to 17th week (growth phase) while feed was restricted from 18th to 26th week (finis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 11 publications
4
16
0
Order By: Relevance
“…The results presented in Table 2 show that no significant differences were found in the analysed hybrid pigs in carcass slaughter value traits and meat basic chemical composition according to RYR1 genotype (CT and CC), which is also confirmed by studies of other authors (Fisher et al 2000;Kusec et al 2005). However, no positive effect of the (Tables 3 and 5), which corroborates the findings pointing to the negative effect of the T allele on meat quality (Oliver et al 1993;Biedermann et al 2000) but is not confirmed in the study of , which shows a similar meat quality of the pigs of CC and CT genotypes.…”
Section: Resultssupporting
confidence: 77%
“…The results presented in Table 2 show that no significant differences were found in the analysed hybrid pigs in carcass slaughter value traits and meat basic chemical composition according to RYR1 genotype (CT and CC), which is also confirmed by studies of other authors (Fisher et al 2000;Kusec et al 2005). However, no positive effect of the (Tables 3 and 5), which corroborates the findings pointing to the negative effect of the T allele on meat quality (Oliver et al 1993;Biedermann et al 2000) but is not confirmed in the study of , which shows a similar meat quality of the pigs of CC and CT genotypes.…”
Section: Resultssupporting
confidence: 77%
“…The differences between the time predicted to achieve 100 kg live weight and the real observed time within the two feeding regimes were not statistically significant, implying that the calculated parameters enabled a good estimation of live weight growth. This is supported by previous results of Kusec et al (2005), who found significant differences between the feeding groups of pigs from the same experiment in average daily intake and gain, feed conversion ratio and in final live weights. Results presented in Table 4 show the frequency of good (real-predicted = 0 days) and false (misestimates for 1-14 and >14 days) predictions of the time period for achieving the selected live weight.…”
Section: Prediction Of Live Weightssupporting
confidence: 81%
“…Busk et al (2000) stated that the carcasses of CT pigs contained more lean and had worse meat quality as compared with the CC pigs. Kusec et al (2005) did not observe significant differences in butchery value of carcasses between the CC and CT pigs; the authors found, however, that meat quality of heterozygous pigs (CT) was worse. Also Krzęcio et al (2005) and Kuhn et al (2005) report poorer quality of meat obtained from CT pigs.…”
Section: Discussionmentioning
confidence: 84%